Development of a method for calculating the safe position of military units by using artificial neural networks based on swarm algorithms - Lytvyn, Vasyl; Uhryn, Dmytro; Iliiyuk, Olexiy; Klichuk, Oleg (Technology audit and production reserves, 2017)
The object of research is development of a method for finding a safe position for military units in combat conditions, using swarm algorithms and neural networks. One of the most problematic places is the complexity of testing the developed method. The difficulty lies in the fact that to check the method in real time, financial costs and military weapons are necessary. The data are obtained due to a multicriteria problem, which allowed to calculate the errors of subjects and objects of research. The obtained results show that the hybrid method allowed to calculate the safe position with greater accuracy, namely by 25–50 % more accurately than using the classical approach. This is due to the fact that the proposed method calculates all possible errors. This makes it possible to obtain the flexibility of the method for finding a safe position. In comparison with the analogous methods known in the formulation of the classical problem of calculating the trajectory and the damage region, only one mathematical value (region, trajectory) is taken into account, and using a hybrid approach one can take into account a number of errors simultaneously. This approach ensures the flexibility of the system and the possibility of expanding a number of mathematical calculations and improving the accuracy of the result.